Pengaruh Integritas Mahasiswa, Motivasi Belajar, Pemahaman Akuntansi dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik (Studi Kasus Pada Mahasiswa Akuntansi FEB PTN dan PTS di Malang) - Hofifah, Nur; Diana, Nur; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2023)
This study aims to determine the effect of student integrity, learning motivation, understanding of accounting, and misuse of information technology on academic fraud behavior. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert Scale. The population in this study were accounting students at the Faculty of Economics and Business at PTN and PTS Universities in Malang. Sampling using the slovin formula obtained the final result as many as 79 respondents. The method of determining the sample is purposive sampling. This data analysis technique uses SPSS 25 for windows. The results of his research show: 1) Variables of Student Integrity, Learning Motivation, Understanding of Accounting and Misuse of Information Technology have a simultaneous effect on Academic Fraud Behavior, 2) Variables of student integrity partially have a positive and significant effect on academic fraud behavior, 3) Variables of learning motivation partially does not have a positive and significant effect on academic fraud behavior, 4) Accounting understanding variable partially has a positive and significant effect on academic fraud behavior, 5) Information technology misuse variable partially has a positive and significant effect on academic fraud behavior.Keywords: Student Integrity, Learning Motivation, Accounting Understanding, and Misuse of Information Technology on Academic Fraud Behavior.